Microbial and metabolic succession on common building materials under high humidity conditions - Simon Lax (Nature Portfolio, 2019)
Microbes inhabit built environments and could contribute to degradation of surfaces especially in damp conditions. Here the authors explore how communities of microbes and their metabolites affect four types of built surfaces under varying environmental conditions.